Peningkatan Keterampilan Pembelajaran Daring Learning Management System Bagi Tenaga Pendidik - Syamsir Nur, Syamsir Nur Syamsir Nur; Ernawati, Ernawati Ernawati; Syamsul Anam, Syamsul Anam Syamsul Anam; Muthalib, Abd Azis Muthalib Azis; Mansyur Asri, Mansyur Asri Mansyur Asri (Vokasi Universitas Halu Oleo, 2023)
The aim of the program is to improve the skills of lecturers in implementing the learning management system (LMS). Activities carried out by the Department of Economics and Development Studies, University of Halu Oleo. The number of participants is 20 lecturers. The activity was carried out in 2 sessions, namely (1) training; and (2) technical guidance. The topics given are class configuration, teaching material management, and class management. On the subject of class configuration, participants carried out practices related to making course rooms in LMS. Meanwhile, in material management topics, a practicum is carried out on how to add to subject topics, and up-load teaching materials, both in file, video, and other learning resource links. Specifically for class management topics, practicum was conducted related to student assignments and attendance configuration. The results of the program show an increase in the ability of participants in managing learning based on LMS. Keywords: system, learning, online